2010
DOI: 10.1194/jlr.m006429
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-related changes in lipid classes with long-chain and very long-chain polyenoic fatty acids in rat spermatogenic cells

Abstract: Mammalian spermatogenesis is an extraordinary cell transformation process. It includes asymmetric division of spermatogonia, rapid proliferation and differentiation into primary spermatocytes, a meiotic phase in which the genetic material in spermatocytes is recombined and segregated to produce haploid cells, a postmeiotic phase in which secondary spermatocytes develop into round spermatids, and differentiation of the latter into late spermatids and spermatozoa ( 1 ). During this last stage, known as spermioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 45 publications
16
57
0
Order By: Relevance
“…These densely packed structures, readily phagocytized by Sertoli cells (Kerr & De Kretser 1974), contain remains of cytoplasm, RNA, former organelles, and neutral lipid inclusions (Russell et al 1990). The spermatid-derived RB are clearly discernible by markers of neutral lipid droplets, in accordance with the finding that they are even richer in TAGs than spermatids (Oresti et al 2010).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…These densely packed structures, readily phagocytized by Sertoli cells (Kerr & De Kretser 1974), contain remains of cytoplasm, RNA, former organelles, and neutral lipid inclusions (Russell et al 1990). The spermatid-derived RB are clearly discernible by markers of neutral lipid droplets, in accordance with the finding that they are even richer in TAGs than spermatids (Oresti et al 2010).…”
Section: Introductionsupporting
confidence: 66%
“…In rodents, classical studies have shown that testicular glycerophospholipids (GPLs) and triacylglycerols (TAGs) become increasingly rich in long-chain polyunsaturated fatty acids (PUFAs) like docosapentaenoic acid during postnatal development, as spermatids contain more of this fatty acid in their GPLs and TAGs than spermatocytes (Beckman et al 1978, Grogan & Huth 1983. Concomitantly, there are also significant changes in unique fatty acids of testicular sphingomyelins and ceramides destined to be components of spermatozoa (Zanetti et al 2010): the proportion of 2-hydroxy very-long-chain PUFA with respect to their nonhydroxy counterparts increases considerably in both lipids from spermatocytes and spermatids (Oresti et al 2010). The regulation of fatty acid biosynthesis and exchange among intracellular organelles of germ cells during spermatogenesis are thus essential for male fertility.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Oresti et al (26) showed, that with progressing differentiation, the amount of polyunsaturated fatty acid-rich GPL per spermatid decreased with the reduction of cell size, whereas the ratio of fatty acids (22:5/20:4) in GPL was increased, but the precise requirements for particular changes in PL composition during spermiogenesis are not yet wellunderstood. The severe morphological defects of seipin-deficient sperm reported here likely result from disturbances in lipid metabolism during spermiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our group has recently reported that SCs produce acetate at high rates [52]. This subject has been overlooked but although the exact role for this acetate produced by SCs remains largely unknown, it is known that developing germ cells exhibit a high rate of lipid synthesis and remodeling during spermatogenesis [153,154]. These peculiarities may also provide targets to develop a male contraceptive.…”
Section: Metabolic Cooperation In Testis As a Concept For Male Contramentioning
confidence: 99%